Students' Perceptions on the Use of Ecological-Based Folklore Digital Learning Media to Strengthen Ecoliteracy - Irpa Anggriani Wiharja; Ira Anisa Purawinagun; Winda Dwi Hudhana; Hamdah Siti Hamsanah Fitriani; Yulian Dinihari (Raja Zulkarnain Education Foundation, 2025)
his study aims to describe high school students' perceptions of the use of ecologically based digital learning media for folklore to strengthen ecoliteracy. The study used a qualitative descriptive method with 53 students in grades X, XI, and XII at Muhammadiyah 3 Senior High School in Tangerang City as subjects. Data were collected using a questionnaire structured based on three main aspects, namely: 1) digital learning media, 2) ecologically based folklore digital learning media, and 3) students' understanding of ecoliteracy through ecologically based folklore digital learning media. Data analysis techniques included data reduction, data presentation, and descriptive conclusion drawing. The results showed that ecologically based digital learning media for folklore positively influenced the learning process; students demonstrated excellent understanding of the material, greater enthusiasm for participation, and improved learning outcomes. In addition, students were able to apply ecological knowledge and values in everyday life. In general, ecologically based digital learning media have proven effective in fostering environmental awareness, strengthening character, and shaping students' ecological behavior, making them relevant as supporting learning media for ecoliteracy at the secondary school level.